Andreev reflection study of the new magnetic superconductor Mo3Sb7: evidence for the gap anisotropy - Dmitriev, V.M.; Rybaltchenko, L.F.; Khristenko, E.V.; Ishchenko, L.A.; Bukowski, Z.; Troć, R. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
We report the point-contact (PC) Andreev-reflection experiments on the new paramagnetic superconductor Mo3Sb7 for which we have observed strong distinctions in the PC spectra measured for different contact axis orientations. Analysis of the PC spectra in the framework of the Blonder—Tinkham—Klapwijk theory has shown that the gap parameter D is strongly anisotropic varying over a very wide range depending on the contact orientation when the maximum Dmax can exceed at least 40 times the minimum Dmin. For these and other reasons we suggest that Mo3Sb7 is not a trivial BCS (s-wave) superconductor but rather has a (s+g)-wave or another unconventional pairing symmetry.